دراسة نمو وتطور ثلاث سلالات من الشعير (Hordeum vulgare L.) ضمن نظم زراعية مختلفة في ظروف المنطقة الساحلية (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
The research was performed by planting three lines of barley (Hordeum vulgare L.) individually or in mixtures with peas (Pisum sativum L.). This study was carried out in Randomized Complete Block Design (RCBD) and four replicates at Dibba Agricultural Research Station between 2016 and 2017. The response of barley lines to these applied farming systems in stem elongation, booting and maturation stages has been studied by measuring the growth and development plant, the competition indices between the studied lines, the dry matter production, the yield and the total relative yield of the lines and the pea contribution (%) in mixtures. The results indicated that the booting stage is the best to produce the highest yield whether in mixed or single farming systems. Barley lines 2 and 3 were superior (P